Design of a Desktop Java-Based Introduction to Basic Electronic Components - Albab, Ulil; Bakhar, Muhammad; Qirom, Qirom (West Science Information System and Technology, 2024)
The development of information technology has had a positive impact on the world of education, one of which is to simplify the learning process. In the field of electronics, understanding basic components is an important foundation for students and practitioners. This Java Desktop-based application design aims to introduce basic electronic components with an easy-to-understand interactive interface. In this software, it contains various information about basic electronic components such as Resistors, Capacitors, Transistors, Diodes, Push Buttons, which is equipped with detailed information about the specifications and basic functions of various electronic components. In addition, the app comes with visual illustrations in the form of images that support the understanding of physical and component symbols. To explain how components in a series work, the app presents interactive animations to clarify the concept of how each component works and functions. During the creation and testing of 5 times, which was carried out using 5 different basic components resulting in different circuits and explanations of how to work, these results then obtained data from these 5 components which were then entered into the MySQL Database. The data present in the Driver Database is displayed using the Desktop-Based Java Programming Language.